PENGARUH POLA MAKAN DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI - Eni Subiastutik; Farika Novita R (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Adolescence is a developmental stage characterized by increased nutritional requirements, making inadequate dietary intake a potential contributor to various health problems, including anemia. This condition remains prevalent among adolescent girls and continues to be a public health concern in Jember Regency, where its occurrence is relatively high. Within this context, dietary quality is considered a modifiable factor that may influence hemoglobin status and warrants further investigation across different adolescent age groups. This study involved 102 female adolescents selected through proportionate stratified random sampling. Information on dietary habits was obtained using a structured questionnaire, while anemia status was determined through hemoglobin measurements using a digital Hb meter. A comparative cross-sectional approach was employed to examine the relationship between dietary patterns and anemia and to compare anemia conditions between early and late adolescents. The collected data were analyzed using ordinal regression. The findings revealed that 50% of respondents had moderately adequate dietary patterns, while 58% demonstrated normal hemoglobin levels. However, anemia was observed more frequently among early adolescents than among late adolescents. Statistical analysis confirmed a significant association between dietary patterns and the occurrence of anemia (p < 0.05). These results indicate that dietary quality plays a substantial role in shaping anemia status among adolescent girls. Therefore, efforts to improve eating habits should be prioritized within health promotion and prevention programs, particularly for age groups that are more vulnerable to anemia. ABSTRAK Masa remaja merupakan periode yang ditandai dengan peningkatan kebutuhan zat gizi, sehingga ketidakseimbangan asupan makanan dapat berdampak pada berbagai masalah kesehatan, termasuk anemia. Kondisi ini masih banyak ditemukan pada remaja putri dan menjadi perhatian di Kabupaten Jember karena prevalensinya yang relatif tinggi. Dalam konteks tersebut, kualitas pola makan dipandang sebagai salah satu faktor yang berpotensi memengaruhi status hemoglobin dan perlu dikaji lebih lanjut pada kelompok usia yang berbeda. Penelitian ini melibatkan 102 remaja putri yang dipilih melalui proportionate stratified random sampling. Informasi mengenai kebiasaan makan diperoleh menggunakan kuesioner, sedangkan status anemia ditentukan melalui pengukuran kadar hemoglobin menggunakan Hb meter digital. Pendekatan cross-sectional digunakan untuk menggambarkan hubungan antarvariabel sekaligus membandingkan kondisi antara remaja awal dan remaja akhir. Data yang terkumpul dianalisis menggunakan regresi ordinal. Hasil pengamatan menunjukkan bahwa 50% responden berada pada kategori pola makan cukup dan 58% memiliki kadar hemoglobin dalam rentang normal. Meskipun demikian, kelompok remaja awal memperlihatkan kecenderungan mengalami anemia lebih besar dibandingkan kelompok remaja akhir. Analisis statistik mengonfirmasi adanya hubungan yang bermakna antara pola makan dan kejadian anemia dengan nilai signifikansi p < 0,05. Temuan ini mengindikasikan bahwa upaya peningkatan kualitas konsumsi pangan memiliki peran penting dalam pengendalian anemia pada remaja putri, terutama pada kelompok usia yang menunjukkan tingkat kerentanan lebih tinggi.